Elite collegiate tennis athletes have lower 2D:4D ratios than those of nonathlete controls - Hsu, C.-C.; Su, B.; Kan, N.-W.; Lai, S.-L.; Fong, T.-H.; Chi, C.-P.; Chang, C.-C.; Hsu, M.-C. (The Journal of Strength and Conditioning Research, 2015)
The ratio of the length of the second finger (index finger) to the fourth finger (ring finger) (2D:4D ratio) is a putative marker for prenatal hormones. Physiological research has suggested a low 2D:4D ratio correlates with high athletic ability. Athletes of specific sports (e.g., American football) have lower 2D:4D ratios than those of nonathletes, whereas athletes of some sports (e.g., rowing, gymnastics, and soccer) do not. This study investigated the 2D:4D ratios among collegiate tennis athletes, elite collegiate tennis athletes, and nonelite collegiate tennis athletes and compared them with nonathletes of both sexes. The participants included 43 elite collegiate tennis athletes (Level I intercollegiate athletes in Taiwan; 27 males and 16 females), 107 nonelite collegiate tennis athletes (Level II athletes; 55 males and 52 females), and 166 nonathlete college students (80 males and 86 females). The principle findings suggest that (a) regardless of sex, collegiate tennis athletes have lower 2D:4D values than those of nonathletes; (b) elite collegiate tennis athletes have lower 2D:4D values than those of nonathletes; (c) among females but not males, athletes and nonelite athletes have lower 2D:4D values than those of nonathletes; and (d) males have lower 2D:4D values than those of females.